2003
DOI: 10.1074/jbc.m209635200
|View full text |Cite
|
Sign up to set email alerts
|

The NF-YB/NF-YC Structure Gives Insight into DNA Binding and Transcription Regulation by CCAAT Factor NF-Y

Abstract: The heterotrimeric transcription factor NF-Y recognizes with high specificity and affinity the CCAAT regulatory element that is widely represented in promoters and enhancer regions. The CCAAT box acts in concert with neighboring elements, and its bending by NF-Y is thought to be a major mechanism required for transcription activation. We have solved the structure of the NF-YC/NF-YB subcomplex of NF-Y, which shows that the core domains of both proteins interact through histone fold motifs. This histone-like pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
258
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(267 citation statements)
references
References 47 publications
5
258
0
4
Order By: Relevance
“…9). Structural studies using mammalian NF-YB and NF-YC heterodimers, the orthologs of Hap3 and Hap5 proteins, respectively, showed that their interaction occurred through histone H2A/H2B-like histone-fold domains (81). Moreover, the Hap32 and Hap5 proteins also could heterodimerize through their histone-fold domains (as reviewed in Ref.…”
Section: Cap2-hap Regulatory Networkmentioning
confidence: 99%
“…9). Structural studies using mammalian NF-YB and NF-YC heterodimers, the orthologs of Hap3 and Hap5 proteins, respectively, showed that their interaction occurred through histone H2A/H2B-like histone-fold domains (81). Moreover, the Hap32 and Hap5 proteins also could heterodimerize through their histone-fold domains (as reviewed in Ref.…”
Section: Cap2-hap Regulatory Networkmentioning
confidence: 99%
“…The CCAAT box is recognized with high affinity and specificity by NF-Y, a heterotrimer composed of NF-YA, NF-YB, and NF-YC, all evolutionarily conserved [12]. NF-YB and NF-YC contain histone fold domains (HFD), structurally related to histones H2B and H2A, and forming a stable histone-like dimer [12]. NF-YA associates to the HFD dimer, conferring CCAAT specificity to the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CCAAT was found in some enhancers before [9,10], it has been mainly considered as a promoter element: it is positioned between À60 and À100 with respect to the transcriptional start site, and the importance is underscored by mutations causing a drop, or complete elimination, of promoter activity [11]. The CCAAT box is recognized with high affinity and specificity by NF-Y, a heterotrimer composed of NF-YA, NF-YB, and NF-YC, all evolutionarily conserved [12]. NF-YB and NF-YC contain histone fold domains (HFD), structurally related to histones H2B and H2A, and forming a stable histone-like dimer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Each subunit has a core region, which has been conserved throughout evolution. The conserved regions of the two subunits NF-YB and NF-YC contain histone fold motifs, which are required for the heterodimerization as a prerequisite for NF-YA association and CCAAT binding (18,34,35). The presence of histone fold motifs in the NF-YB and NF-YC implicates these proteins as being likely to have multiple protein-protein interactions with other transcription factors as well as being given protein modifications.…”
Section: Discussionmentioning
confidence: 99%